(untitled) (Journal of Information Technologies in Education (ITE), 2016)
The problem of organization of teacher’s professional activity in innovative educational environment is revealed in the article. The fundamental definitions of the concept of "innovative educational environment" in different aspects are determined. The analysis of researches of primary school teacher’s training in Ukraine and highly developed countries of the world is witnessed a number of contradictions that outlined necessity to generate the innovative (information) educational environment. Effective organizational and methodical decision in formation of competitive teacher is the introduction subject "Methods of organization of teacher’s professional activity in conditions of innovative educational environment" to educational process of primary school teacher’s training. Its aim, objectives,information scope, requirements to level of mastering of content component, methods and forms of monitoring and evaluation of students’ competency have been revealed. The course is based on designed innovative IT-based (cloudy-oriented) environment of pedagogical training of primary school teachers, and cloudy-oriented products are integrated in it, that will make the learning process interactive: OneNote, Skype, GoogleDisk, SkyDrive,teacher’s personal website, OneNote. The managing of students’ mastering process of pedagogical subjects is performed at lessons and using teacher’s electronic classroom.